PERTUMBUHAN DAN HASIL BAWANG MERAH (ALLIUM ASCALONICUM L.) TERHADAP PEMBERIAN BERBAGAI DOSIS PUPUK NPK - Irma, Irma; Pasigai, Muhammad Anshar; Mas’ud, Hidayati (AGROTEKBIS, 2018)
Red onion (Allium ascolanicum L.) is one of the leading vegetable commodities that farmers have long been cultivated intensively.The low productivity of onion due to cultivation techniques conducted at the field level is not adequate, and the use of NPK inorganic fertilizers is still diverse. One alternative that can be done to improve the growth and yield of onion is the choose of the right type of NPK fertilizer. This study aims to obtain a proper dose of NPK fertilizer on the growth and yield of onion crops. This research was conducted in Sidera village, Biromaru sub district, Sigi regency, Central Sulawesi province, This research used Randomized Block Design (RAK) consisting of 5 treatment levels: P0 = control, P1 = 75 kg.ha-1 of NPK fertilizer, P2 = 150 kg.ha-1 NPK fertilizer, of P3 = 225 kg.ha- 1 of NPK fertilizer, and P4 = 300 kg.ha-1 of NPK fertilizer. All treatments were repeated 4 (four) times, so overall there were 20 experimental units.The results showed that the dosage of NPK fertilizer of 300 kg.ha-1 had a significant effect (the best) on the growth and the yield of onion crop that indicated by the average plant height of 33.10 cm, average number of leaves of 22,50 strands, total dry weight of 6.02 g, total tuber per hill of 6.13 fruit, tuber weight per hill of 25.48 g, and tuber yield per hectare of 12,06 ton.ha-1 .Â Keywords: Onion, NPK Fertilizer.